Bioregion, Biopolitics, and the Creaturely List: The Trouble with FaunaWatch - MacDonald, Tanis (Studies in Canadian Literature / Études en littérature canadienne, 2014)
Canada’s tradition of nature poets who are also philosophically astute (or, conversely, philosophical poets who are astute about bioregionality) is long and would include Don McKay, Tim Lilburn, and Jan Zwicky, to name just a few. My own practice of observing and archiving animals, and writing about such archiving practices, an ongoing project called FaunaWatch, has made it clear that nothing about doing so is simple, just as nothing about being the owner-operator of a fleshy body is simple. This essay examines my practice of observation and archiving a bioregional creaturely list as an important critical and creative process, though one that is powered by an acquisitive energy, raising questions about the culture of sighting and “collecting” sights. FaunaWatch, as practice and as project, has increased in complexity precisely because of its humble (and humbling) beginnings, growing as it did out of my intense desire to fix myself in the realities of my geographical location in southwestern Ontario. When a hybrid of scholarly discourse and bioregional presence goes into the woods, it is no real surprise to find the organic impulse of the poem and the biological organism, the animal self and the animal other, undermined by uncertainty.